Morphological Characteristics of Batuah Red-Fleshed Durian (Durio graveolens), an Endemic Exotic Plant from East Kalimantan, Indonesia - Kurniadinata, Odit Ferry; Wenpei, Song; Rusdiansyah, Rusdiansyah (Journal of Tropical Horticulture, 2020)
Kalimantan Island is rich in genetic resources and species diversity of Durio spp. plant. The large number of Durio species that grow in Kalimantan illustrates that this area is the most important distribution center for durian relatives. The best-known edible durians are Durian (Durio zibethinus). However, Kalimantan also has various types of Durian that are not yet widely known and have superior potential. One of the unique and exotic plants is the red flesh Durian in East Kalimantan, Indonesia. The fruit of this plant is unique because it has red flesh. At present, there is no morphological identification of this East Kalimantan Durio graveolens plant. The study aimed to identify the morphological character of Batuah D. graveolens from East Kalimantan, Indonesia. This research was carried out by collecting data and information about the morphological characteristics of the plant and fruits. The results of the study successfully identified Batuah D. graveolens from East Kalimantan as a plant diverts from another Durio spp. plant known like D. zibethinus and D. kutejensis especially for red flesh character.